Anthropology and Design: Exchanges, Entanglements, and Frictions - Ivan Bargna; Giovanna Santanera (Antropologia)
Nowadays, cultural anthropologists and designers are more connected than ever. It is not unusual to find them working side by side on the same team, together with engineers, marketers and other business operators. How did we get to this point? What are the research threads that opened the way to this intersection between design and anthropology? Where are we heading now? In this introductory essay, we trace the history of the mutual attraction between anthropology and design, highlighting connections, exchanges as well as frictions and pitfalls. After taking into consideration some research routes and transdisciplinary projects, we examine the limits of the current collaborations between anthropologists and designers. Finally, as cultural anthropologists we reflect on how the intersection between anthropology and design has led to a more general rethinking of cultural anthropology, in relation to both its object (humans and culture) and its method (ethnography). This rethinking goes far beyond the specific field of design anthropology, hinting at the emergence of an anthropology of the future.